The effect of online learning on student learning outcomes on the theme of objects around us - Novianti, Yusda; Ramadhan, Nuri; Muhajir, Moch (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2021)
This study aims to determine the effect of online learning on learning outcomes of objects around us in fifth-grade elementary school students. The subjects of this study were the fifth-grade students of MIS Al-Khairiyah, totaling 36 people, consisting of 19 males and 17 females. This study uses descriptive quantitative research with data testing using SPSS 25. Data were obtained through questionnaires, data from schools, and interviews. The data analysis consists of validity, normality, and hypothesis testing. The Kolmogorov Smirnov normality test results are known to have Sig = 0.200 0.05, so it can be concluded that the residual value is normally distributed. The hypothesis test results show that the value of fcount and ftable = 69.234 4.121. From the test results, it can be concluded that online learning significantly affects student learning outcomes. The coefficient of determination is 0.671, which means that online learning can explain student learning outcomes by 67.1%. This research contributes to developing the e-learning process in education for the better.